De plantes dignes et d’invasions barbares : Les sociétés au miroir du végétal - Juliet J. Fall; Laurent Matthey (VertigO)
This paper deals with the increasing trend of granting a moral status to plants, morally ranked and stratified. We explore three thematic interconnected fields that together participate in working through a dynamic and moral conception of the plant life. In order to do this, we take the example of so-called invasive species, and read this example in three ways : the tension between the controlled and controllable ; the link between names and things, that is to say the modalities of categorisation of ‘reality’ within scientific practices ; and finally the dialectics of production and consumption of social practices. This leads us to call for a better understanding of the reception of expert discourses and regulatory norms in the field of biodiversity conservation related to invasive species.